A Chinese pedigree with Brown-Vialetto-Van Laere syndrome due to two novel mutations of SLC52A2 gene: clinical course and response to riboflavin - Kaili Shi; Zhen Shi; Huifang Yan; Xiaodong Wang; Yanling Yang; Hui Xiong; Qiang Gu; Ye Wu; Yuwu Jiang; Jingmin Wang (BMC, 2019)
Abstract Background Brown-Vialetto-Van Laere Syndrome (BVVLS), a rare neurological disorder characterized by motor, sensory, and cranial neuronopathies, is mainly associated with defective riboflavin transporters encoded by SLC52A2 and SLC52A3 genes. Clinical outcomes have been shown to be improved significantly by high-dose riboflavin supplementation. The aim of this study was to identify genetic causes and further evaluate the clinical course and response to riboflavin in a Chinese pedigree with BVVLS. Case presentation We report the novel compound heterozygous variants c.1328G>A p.(Cys443Tyr) and c.1022_1023insC p. (Leu341Profs*103) of SLC52A2 gene in a female proband who presented in our out-patient clinic at the age of one-year-old with progressive mental and motor regression, breath holding, and brain stem dysfunction including facial weakness, hearing loss, dysphagia. Following high-dose riboflavin supplementation, the respiratory insufficiency and mental, motor, and bulbar function improved. However, sensorineural hearing loss was not improved. The missense variant site was highly conserved. Both variants were not found in the population database gnomAD. The two variants were inherited from her mother and father, respectively. Both variants were predicted to be deleterious by Polyphen2, Mutation taster, and SIFT and were classified as likely pathogenic according to the ACMG guideline. Conclusions Two novel pathogenic variations of SLC52A2 gene were firstly found from a Chinese pedigree with BVVLS. Clinical outcomes could be improved by early diagnosis and riboflavin supplementation.